Analisis Optimalisasi Pengelolaan Aset/Barang (Barang Milik Negara) di Kantor Dinas Pekerjaan Umum Provinsi Jambi - Etik Winarni; Yolanda Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Good asset management will contribute greatly to local governments, on the contrary if the management is bad it will also have a negative impact on the local government. Based on the background above, the researcher is interested in further analyzing the "Analysis of Optimizing the Management of Assets / Goods (State Property) in the Office of the Provincial Public Works Office of 2017-2018". Data were analyzed using validity and reliability tests for questionnaire data and Multiple Linear Regression analysis. From the results of the analysis of the results of the analysis and discussion of research on the optimality of asset management (State Property) at the Office of Public Works and Public Housing in Jambi Province which includes planning, implementation, as well as guidance, supervision, control, it can be concluded that the first hypothesis states that there is no influence significant between the planning of the optimal level of management of assets / goods (State Property) in the office of the Public Works and Housing Agency of Jambi Province in this study proved, because it does not have a positive and insignificant effect. The second hypothesis states that it has a significant influence between implementation of the optimal level of management of assets / goods (State Property) in the office of the Public Works and Public Housing Office of Jambi Province in this study is proven, because it has a positive and significant effect. The third hypothesis which states that has a positive and significant influence between the Development, supervision and control of the optimal level of management of assets / goods (State Property) at the Office of Public Works and Public Housing in the Province of Jambi in this study is proven, because it has a positive influence and significant.